Use of past collective traumas, fear and conspiracy theories for securitization of the opposition and authoritarianisation: the Turkish case. Issue 2 (17th February 2022) - Yilmaz, Ihsan; Shipoli, Erdoan
ABSTRACT: Several studies have analysed different aspects of Turkey's authoritarianisation under the AKP rule. However, there is still a gap in this literature with regards to the role of instrumentalization of narratives and discursive strategies in this authoritarian turn which has been successfully engineered by the AKP. This article addresses this gap and shows how securitizing narratives based on fear, trauma, nostalgia, ontological insecurity, grievances, and conspiracy theories have been used by President Erdoğan and his AKP as psycho-political tools of authoritarianisation. It argues that these tools have shown to be useful in securitizing the opposition to consolidate power, change the governing structure, and take other extraordinary measures, while legitimizing these acts for the public. In an attempt to provide a holistic picture, this article analyses how the AKP has securitized almost all of the significant opposition socio-political identities, groups and parties in Turkey. This study contributes to securitization theory by shedding light on the use of traumas, conspiracy theories, and fear in the securitization process, in legitimizing securitization and authoritarianisation.